The Canadian Index of Wellbeing: A Better Way to Assess and Communicate the Value of Libraries - Bradley, Cara (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2021)
Historically libraries have struggled to communicate their value in ways meaningful to both policy-makers and the general public. Traditional measures like collection and circulation counts, while useful, fail to capture libraries’ full impact on the lives of their users. The recent dominance of Gross Domestic Product (GDP) as the prevailing metric for policy and decision-making frames library value in exclusively economic terms. However, it is overreliance on economic measures like GDP in library assessment that leads to their undue underfunding. Meanwhile a tool like the Canadian Index of Wellbeing (CIW) is a credible alternative metric that shifts the focus from the purely economic toward additional facets of life. Developed through a broad cross-Canada consultation process, the CIW uses eight domains affecting wellbeing: community vitality, democratic engagement, education, environment, healthy populations, leisure and culture, living standards, and time use. Compared with the narrow economic focus of GDP, the CIW is a powerful tool to communicate the true value of public libraries and the impact they have on their users.